Analysis of The Influence of Attitudes and Perceptions on Decisions to Use Sharia Fintech Peer to Peer Lending in Indonesia with Satisfaction As an Intervening Variable - Dedy Dwi Arseto; Andri Soemitra (LPPM Institut Nasional Laa Roiba Bogor, 2022)
This study aims to examine the Influence of Attitudes and Perceptions on Decisions to Use Sharia Fintech Peer To Peer Lending in Indonesia. With Satisfaction as an Intervening Variable. Data analysis in this research is quantitative analysis using Partial Least Square (PLS) analysis test tool. The object of this research is Peer To Peer Lending Syariah Fintech users in Indonesia. The sample was taken using the proportioned cluster sampling method, where the sample taken was only Sharia peer-to-peer (P2P) fintech users up to 100 samples. From the results of the research conducted, it shows that Attitudes, Perceptions affect the satisfaction of Fintech Syariah Peer To Peer Lending in Indonesia. Satisfaction affects the decision to use Sharia Fintech Peer To Peer Lending in Indonesia. Attitude influences the satisfaction of Fintech Syariah Peer To Peer Lending in Indonesia. Perception does not affect the decision to use Sharia Fintech Peer To Peer Lending in Indonesia. Satisfaction can mediate the relationship between attitudes towards the decision to use Sharia Fintech Peer To Peer Lending in Indonesia. Satisfaction can mediate the relationship between perceptions of decisions to use Sharia Fintech Peer To Peer Lending in Indonesia.